2019
DOI: 10.1017/psrm.2019.51
|View full text |Cite
|
Sign up to set email alerts
|

Technology and protest: the political effects of electronic voting in India

Abstract: Electronic voting technology is often proposed as translating voter intent to vote totals better than alternative systems such as paper ballots. We suggest that electronic voting machines (EVMs) can also alter vote choice, and, in particular, the way in which voters register anti-system sentiment. This paper examines the effects of the introduction of EVMs in India, the world's largest democracy, using a difference-in-differences methodology that takes advantage of the technology's gradual introduction. We fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Distinguishing between overall and effective turnout is particularly pertinent when comparing paper versus Internet voting, as the use of voting machines constitutes an effective method for reducing voter errors and uncounted ballots (Alvarez and Hall 2008 ; Germann 2020 ). This empirical link between e-voting and the share of invalid votes has been confirmed for various countries, such as Belgium (Dandoy 2014 ; Dejaeghere and Vanhoutte 2016 ), Brazil (Nicolau 2015 ; Fujiwara 2015 ; Katz and Levin 2018 ), India (Desai and Lee 2019 ), the Netherlands (Allers and Kooreman 2009 ), and the USA (Kimball et al 2004 ; Stewart 2006 ). Given that this note focuses on Internet voting, we also test the impact our independent and control variables have on the share of Internet voters per district.…”
Section: Methodsmentioning
confidence: 85%
“…Distinguishing between overall and effective turnout is particularly pertinent when comparing paper versus Internet voting, as the use of voting machines constitutes an effective method for reducing voter errors and uncounted ballots (Alvarez and Hall 2008 ; Germann 2020 ). This empirical link between e-voting and the share of invalid votes has been confirmed for various countries, such as Belgium (Dandoy 2014 ; Dejaeghere and Vanhoutte 2016 ), Brazil (Nicolau 2015 ; Fujiwara 2015 ; Katz and Levin 2018 ), India (Desai and Lee 2019 ), the Netherlands (Allers and Kooreman 2009 ), and the USA (Kimball et al 2004 ; Stewart 2006 ). Given that this note focuses on Internet voting, we also test the impact our independent and control variables have on the share of Internet voters per district.…”
Section: Methodsmentioning
confidence: 85%
“…One is different ballot designs, assuming that more complexity results in more voting mistakes (Herron and Sekhon 2005; Herrnson et al 2012; Pachón et al 2017). This assumption implies that technological advancements should reduce invalid voting (Desai and Lee 2021) and is accompanied by the observation that invalid voting is generally segmented by voters’ education level (McAllister and Makkai 1993; Fatke and Heinsohn 2017). Yet, this relationship is nondeterministic, as the introduction of simplified ballots in 1990s Brazil, for example, did not reduce invalid ballots.…”
Section: Literature Review and Latin American Trendsmentioning
confidence: 99%
“…For elections in which the relationship between voting technology and the invalid vote share is indisputably strong, we know little about the electoral reaction of voters wishing to cast invalid ballots when this option is removed. Desai and Lee (2017) moved this issue forward by studying the behavior of voters wishing to invalidate their votes when the option of casting a null vote is removed. Specifically, they studied the behavior of Indian voters who intentionally invalidated their votes in paper ballot systems under an electronic voting system that prevented casting a null vote (Desai and Lee 2017).…”
Section: Political Effects Of Voting System Choicementioning
confidence: 99%
“…Desai and Lee (2017) moved this issue forward by studying the behavior of voters wishing to invalidate their votes when the option of casting a null vote is removed. Specifically, they studied the behavior of Indian voters who intentionally invalidated their votes in paper ballot systems under an electronic voting system that prevented casting a null vote (Desai and Lee 2017). They found that the introduction of electronic voting led this subset of voters to cast their ballots for nonviable or nonestablishment parties.…”
Section: Political Effects Of Voting System Choicementioning
confidence: 99%